Teh Celup Daun Pepaya (Carica papaya) Solusi Alami Antihipertensi di Dusun Tanah Abang, Desa Mersam - Trifah, Rahmadha; Marisanti, Debi Putri; Siti Nurul Khoiriyah; Bella Melyani; Prima, Nurmalinda; Hutagalung, Bertha Uli; Ningsih, Ayi Setiya; Verra Veriska, Pretty Sepvanny; Devianti, Dina Nazifa; David Usmany, Abdillah (Universitas Baiturrahim, 2025)
A community service activity with the theme